A Case Report of COVID-19 in New Orleans, Louisiana: Highlighting the Complexities of Prognostication in a Critically Ill Patient - Zachary I. Lerner; Rebecca V. Burke; Jonathan McCall; Alexandra Leigh; Marcia Glass (Palliative Medicine Reports, 2020)
Palliative care teams and intensive care teams have experience providing goals-of-care guidance for critically ill patients and families. Critical coronavirus disease 2019 (COVID-19) infection is defined as infection requiring intensive care unit care, respiratory support, and often multiorgan involvement. This case presents a 53-year-old critically ill COVID-19 patient in multisystem organ failure who appeared hours from death despite best medical efforts. Comfort-focused care and compassionate extubation were offered after all medical teams felt near certain that death was imminent. Overnight, while options were being considered by the family, the patient began to markedly improve hemodynamically and was extubated several days later. Weeks later, the patient survived the hospital stay and was discharged to rehabilitation. After rehabilitation he returned home, able to walk, communicate freely, and independently perform all activities of daily living. Dialysis was no longer necessary and was stopped. The challenges of assisting in goals-of-care conversations for patients with serious COVID-19 infection are discussed.